Single-Center Experience in the Endovascular Management of the Combination of Isolated Common and Internal Iliac Artery Aneurysms - Wang, Wei; Wu, Jianqiang; Shao, Jiang; Xu, Fang; Chen, Yuexin; Liu, Bao; Zheng, Yuehong (Frontiers in Surgery, 2021)
Objective: The combination of isolated common and internal iliac artery aneurysms (CIIAA) are rare, life-threatening, abnormal conditions with relatively complex treatment. This study aimed to evaluate the clinical characteristics and treatment outcomes of CIIAA. Methods: We retrospectively reviewed 26 patients with CIIAA consecutively treated between January 2010 and August 2020 at Peking Union Medical College Hospital. Demographic, clinical characteristic, treatment strategy and outcome data were collected and analyzed. Results: Twenty-six patients (24 men and 2 women) with a mean age of 70 years were included. There was a total of 72 aneurysms, and the mean diameters of the common iliac artery aneurysms (CIAA) and internal iliac artery aneurysms (IIAA) were 36 mm and 38 mm, respectively. Ten patients (38%) presented with bilateral CIAA and unilateral IIAA, and eight (31%) had CIAA with ipsilateral IIAA. All patients were treated with endovascular repair, and the overall primary technical success rate was 100%. The surgical techniques mainly included combined bifurcated stent grafting and embolization (n=11), combined straight stent grafting and embolization (n=8), and IIA reconstruction (n=7). There were no patient deaths or reintervention during hospitalization. The mean follow-up time was 43 months, and the patency rate of the stent was 96.2%. The overall reintervention rate was 7.7%. During the follow-up period, there were no aneurysm-related deaths. Conclusions: Endovascular repair involving stent graft placement, coil embolization and IIA revascularization is a safe and effective treatment for isolated CIIAA.